FUNGSI MOTIF PENGHAKIMAN ALLAH DI 2 TESALONIKA 2:1-12 MENURUT PENDEKATAN ANALISIS WACANA - Alexander Darmawan Limasaputra (Jurnal Amanat Agung, 2021)
Abstract: This article discusses about the function of the motive of God's judgment found in 2 Thessalonians 2:1-12. The research analysis in this article uses a discourse analysis approach. Discourse analysis is a broad umbrella for all methods to analyze languages not from the level of words or sentences, but at a higher level, namely to analyze the relationships between sentences, paragraphs, broader units and the text as a whole. The aspects of discourse analysis used in this article are discourse markers and information structure analysis. Discourse analysis approach is useful especially because the Epistle of 2 Thessalonians is used by Paul as a mean of communication to the Thessalonians. The analysis results of this article will explain that the function of God's judgment in 2 Thessalonians 2:1-12 is to comfort and strengthen the Thessalonians so that their faith is not shaken and they do not fear the claims that the day of the Lord has come.Keywords: discourse analysis, discourse markers, information structure analysis, God's judgment, 2 Thessalonians. Abstrak: Artikel ini membahas fungsi motif penghakiman Allah yang terdapat di 2 Tesalonika 2:1-12. Analisis penelitian di dalam artikel ini menggunakan pendekatan analisis wacana (AW). AW merupakan payung besar untuk semua metode yang menganalisis bahasa bukan dari tingkat kata atau kalimat, tetapi menganalisis bahasa dengan tingkat yang lebih tinggi daripada kata dan kalimat, yaitu menganalisis hubungan antar kalimat, paragraf, unit yang lebih luas dan teks secara keseluruhan. Aspek AW yang digunakan dalam artikel ini adalah analisis markah wacana dan analisis struktur informasi. Pendekatan AW bermanfaat terkhusus 2 Tesalonika merupakan sebuah surat yang menjadi alat komunikasi Paulus kepada jemaat Tesalonika. Hasil analisis dalam artikel ini akan memperlihatkan bahwa fungsi motif penghakiman Allah di 2 Tesalonika 2:1-12 adalah menghibur dan menguatkan jemaat Tesalonika supaya mereka tidak guncang dan takut dari klaim palsu yang menyatakan hari Tuhan telah tiba.Kata-kata kunci: analisis wacana, markah wacana, analisis struktur informasi, penghakiman Allah, 2 Tesalonika.